A review of managing carbon emissions for sustainable supply chain management - Prabawathi, Raman; Fatimah, Mahmud; Shabir, Shaharudin (Penerbit Universiti Malaysia Pahang, 2023)
Carbon emissions were one of the most critical contributors to climate change, and the recent climate agreement had agreed for all participating countries to reduce their emissions. Malaysia has pledged to reduce 45 per cent of its carbon emissions by 2025. However, reducing carbon emissions from the industry was still limited due to voluntary reporting, particularly among manufacturers. Thus, it is ambitious for the Malaysian government to achieve its target by 2025. A complete review is performed to go through the literature and determine the review's research path. This review aims to investigate the low carbon performance based on the manufacturing industry's low carbon supply chain practices. The findings show that low carbon production was insignificant in reducing overall carbon emissions. In contrast, the rest of the low carbon supply chain practices were by the Natural Resource-Based-View (NRBV) theory. It helps to identify companies' low carbon supply chain practices to reduce carbon emissions and meet environmental regulations. Additionally, the review also provided new insight into mediating effect that contributes to the organizational theory of NRBV. The theoretical hypotheses were tested with bias-corrected and accelerated (BCA) bootstrap confidence intervals. The instrument used in this review is a questionnaire, and the questionnaire consists of five (5) scales which tapped on (LCSCM), energy management, and low carbon performance. Responses from the respondent were collected via an online survey between Malaysian manufacturing industries. SmartPLS was used to perform the model and structural analyses. The result shows that LCSCM influence carbon performance directly and indirectly, so the hypotheses are supported. This review is one of the earliest attempts to record empirical evidence regarding companies’ low carbon supply chain practices and performance. Thus, the review shows results can be used and extended to develop low-carbon supply chain frameworks.